2017
DOI: 10.1039/c7ra03213g
|View full text |Cite|
|
Sign up to set email alerts
|

Adsorption properties of NO molecules on the hexagonal LaCoO3(0 0 1) surface: a density functional theory study

Abstract: Six types of adsorption configurations, together with two different adsorption sites for NO adsorption on LaCoO3, were investigated via density functional theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In order to explore catalytic mechanism, some work has been done to investigate the reaction between adsorbed NO molecule and LaCoO 3 surface by employing the density functional theory (DFT) method [12,21,22,23]. Liu et al [21] found that the adsorption of NO on the LaCoO 3 surface is accompanied by the formation of bonds such as Co-N, Co-O, and O-N. The surface reactivity of doped perovskites may have some differences from that of undoped perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore catalytic mechanism, some work has been done to investigate the reaction between adsorbed NO molecule and LaCoO 3 surface by employing the density functional theory (DFT) method [12,21,22,23]. Liu et al [21] found that the adsorption of NO on the LaCoO 3 surface is accompanied by the formation of bonds such as Co-N, Co-O, and O-N. The surface reactivity of doped perovskites may have some differences from that of undoped perovskites.…”
Section: Introductionmentioning
confidence: 99%